2004
DOI: 10.1016/j.jtcvs.2003.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent multiple left atrial focal activations with fibrillatory conduction and right atrial focal or reentrant activation as the mechanism in atrial fibrillation

Abstract: Multiple left atrial focal activations with fibrillatory conduction and right atrial focal or reentrant activations are the mechanism in permanent atrial fibrillation associated with mitral valve disease. Intraoperative mapping would facilitate the indication for simplified procedures confined to the left atrium or the pulmonary veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 19 publications
(17 reference statements)
6
78
0
Order By: Relevance
“…2,13,19 The study by de Groot et al 2 postulates transmural conduction of fibrillation waves as the leading mechanism of epicardial breakthrough, whereas many others use radial spread of activation as criterion to identify ectopic focal discharges during AF. [20][21][22][23][24] Using radial spread of activation and QS electrogram morphology as criterion for ectopy, Lee et al 25 recently demonstrate that AF in dogs undergoing vagal stimulation can be maintained by multiple ectopic foci.…”
Section: Discussionmentioning
confidence: 99%
“…2,13,19 The study by de Groot et al 2 postulates transmural conduction of fibrillation waves as the leading mechanism of epicardial breakthrough, whereas many others use radial spread of activation as criterion to identify ectopic focal discharges during AF. [20][21][22][23][24] Using radial spread of activation and QS electrogram morphology as criterion for ectopy, Lee et al 25 recently demonstrate that AF in dogs undergoing vagal stimulation can be maintained by multiple ectopic foci.…”
Section: Discussionmentioning
confidence: 99%
“…7 In addition, Sahadevan et al 36 have observed regular short CL activity, predominantly from the LA, in patients with chronic AF and suggested that the posterior LA may be responsible for maintaining chronic AF. However, Nitta et al 37 have observed the existence of multiple LA and RA focal activations in patients with permanent AF and mitral valve disease that may explain the maintenance of AF despite ablation in these patients.…”
Section: Frequency Mapping To Identify Sources Maintaining Afmentioning
confidence: 99%
“…6 In the present study, we could only compare the histopathological changes of the LAA with those of the left atrial free wall using samples from the autopsy controls without AF. No significant differences were found between these areas except for endocardial thickening.…”
Section: Causes Of Histopathological Alterations Of the Laa With Valvmentioning
confidence: 99%
“…In addition, patients do not usually require postoperative anticoagulant therapy. 4 The pulmonary veins are believed to be the origin of repetitive activation, 5,6 and the left atrial appendage (LAA) is frequently the source of thrombi for systemic embolism. Therefore, in the maze operative procedure for AF, the pulmonary veins are isolated and the atrial appendages are excised.…”
mentioning
confidence: 99%